PERBANDINGAN PERSEPSI TENTANG VAKSIN COVID-19 PADA MASYARAKAT DESA LANSOT DAN LANSOT TIMUR KEC. TARERAN KAB. MINAHASA SELATAN - Ratinsulu, Regil Claudeo Carmel; Pangemanan, Melki; Salam, Ilham (JURNAL ILMIAH KESEHATAN MANADO, 2024)
Vaccines are one of the preventive measures in overcoming the Corona Virus Disease (Covid-19) pandemic problem. Public perception about the Covid-19 vaccine will influence a person's attitudes and behavior in receiving the Covid-19 vaccine. Everyone who has a good perception will definitely accept the vaccine and if people's perception is not good they will definitely refuse and not want to be vaccinated. The aim of this research is to compare perceptions about the Covid-19 vaccine among the people of Lansot and East Lansot Villages, Tareran District. This research is a descriptive quantitative research with a cross-sectional approach carried out in Lansot and East Lansot Villages in January-March 2023 on 86 respondents who were analyzed using univariate and bivariate analysis with the independent sample t-test. The research results obtained a sig value. 0,000. The conclusion is that there is a comparison of perceptions about the Covid-19 vaccine among the people of Lansot and East Lansot Villages, Tareran District. Continuous education is needed among the public to provide a good understanding of the Covid-19 vaccine so that the public can also have a good perception of the Covid-19 vaccine.